2019
DOI: 10.1186/s12866-019-1679-0
|View full text |Cite
|
Sign up to set email alerts
|

The sensor kinase BfmS controls production of outer membrane vesicles in Acinetobacter baumannii

Abstract: BackgroundAcinetobacter baumannii is an important opportunistic pathogen responsible for various nosocomial infections. The BfmRS two-component system plays a role in pathogenesis and antimicrobial resistance of A. baumannii via regulation of bacterial envelope structures. This study investigated the role of the sensor kinase, BfmS, in localization of outer membrane protein A (OmpA) in the outer membrane and production of outer membrane vesicles (OMVs) using wild-type A. baumannii ATCC 17978, ΔbfmS mutant, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…The K locus is regulated by the two-component signal transduction system BfmRS. The global BfmR regulator, along with histidine kinase BfmS, controls a variety of processes, including biogenesis of A. baumannii envelope elements, formation of biofilms, desiccation tolerance, and multiple stress responses [ 46 , 47 , 48 , 49 ]. Several studies demonstrated that the production of capsules affects A. baumannii virulence and persistence in the host [ 50 , 51 ].…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
“…The K locus is regulated by the two-component signal transduction system BfmRS. The global BfmR regulator, along with histidine kinase BfmS, controls a variety of processes, including biogenesis of A. baumannii envelope elements, formation of biofilms, desiccation tolerance, and multiple stress responses [ 46 , 47 , 48 , 49 ]. Several studies demonstrated that the production of capsules affects A. baumannii virulence and persistence in the host [ 50 , 51 ].…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
“…OMVs are one of the research hotspots of microbial neighborhood in recent years, which are considered to be closely related to the virulence and pathogenicity of bacteria. In Acinetobacter baumannii, OMVs can provide more protection to the existing defense system under antibacterial pressure, and OMVmediated cytotoxicity of host cells and production of OMVs can be regulated by the BfmRS twocomponent system [10,11]. OMVs can also be produced by bacteria in internal and external environments, but the production of OMVs is a secretion process controlled by the environment [12], so different OMVs extraction methods have a certain impact on the number and content of OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation into competent cells allows transposome entry ( Gallagher, 2019 ) however, this step cannot be easily performed in a high through-put manner leading to a preference for conjugation-based protocols ( Kazi et al, 2020 ). One vector-based Tn 5 systems also exist; pRL27 system in ATCC ® 17978 TM ( Kim et al, 2019 ) which can either be delivered to A. baumannii through electroporation or conjugation. Kim et al mutagenized ATCC ® 17978 TM and screened for loss of biofilm formation leading to the establishment of BfmRS two-component system’s role in outer membrane vesicle (OMV) production ( Kim et al, 2019 ).…”
Section: High-throughput Genetic Screeningmentioning
confidence: 99%
“…One vector-based Tn 5 systems also exist; pRL27 system in ATCC ® 17978 TM ( Kim et al, 2019 ) which can either be delivered to A. baumannii through electroporation or conjugation. Kim et al mutagenized ATCC ® 17978 TM and screened for loss of biofilm formation leading to the establishment of BfmRS two-component system’s role in outer membrane vesicle (OMV) production ( Kim et al, 2019 ).…”
Section: High-throughput Genetic Screeningmentioning
confidence: 99%
See 1 more Smart Citation